2015
DOI: 10.1111/aas.12529
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally applied opioids for postoperative pain: evidence of an analgesic effect? A systematic review and meta‐analysis

Abstract: Evidence of a clinically relevant analgesic effect of peripherally applied opioids for acute postoperative pain is lacking. The analgesic effect of peripherally applied opioids may depend on the presence of preoperative inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…38 In humans, a meta-analysis of peripherally-delivered opioids for postoperative pain found that preoperative inflammation was a key factor in determining postoperative analgesic outcomes. 39 Accordingly, we report here that the potencies of both loperamide and oxymorphindole were increased following inflammation, such that ED 50 values following complete Freund's adjuvant are approximately three-to six-fold lower in inflamed than in naïve mice. This holds true for both drugs, as well as for both intraplantar and subcutaneous routes of administration.…”
Section: Discussionmentioning
confidence: 70%
“…38 In humans, a meta-analysis of peripherally-delivered opioids for postoperative pain found that preoperative inflammation was a key factor in determining postoperative analgesic outcomes. 39 Accordingly, we report here that the potencies of both loperamide and oxymorphindole were increased following inflammation, such that ED 50 values following complete Freund's adjuvant are approximately three-to six-fold lower in inflamed than in naïve mice. This holds true for both drugs, as well as for both intraplantar and subcutaneous routes of administration.…”
Section: Discussionmentioning
confidence: 70%
“…Carrageenan elicits an endogenous inflammatory response that mimics that which occurs naturally, suggesting that the nonresponsive state of the peripheral DOR system could also occur in inflammatory conditions where 12-/15-LOX metabolites of AA are generated, such as rheumatoid arthritis (Deleuran et al, 1994;Liagre et al, 1997) and osteoarthritis (Kelly et al, 2015). It is possible that a LOX-dependent nonresponsive state of peripheral opioid receptor systems may underlie the cases where some clinical studies have failed to demonstrate effectiveness of peripherally restricted opioids for the treatment of pain (for reviews, see Vadivelu et al, 2011;Nielsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…e increased concentration of GLU and cortisol after operation indicated that besides nerve conduction regulating stress response, local inflammatory response was also related to cytokine release. erefore, a variety of measures were taken to reduce stress response after surgery [22,23]. e results of this study showed that preoperative analgesia could effectively reduce stress state of patients and oxycodone could effectively inhibit stress response.…”
Section: Discussionmentioning
confidence: 86%